The Acceptance of Difference in School: Conditions to Contribute More Pedagogical Encounters - Gómez-Ramos, Daniel (Revista Electrónica Educare, 2021)
This paper addresses the concern about the care of the other and the responsibility for children’s lives as the core of education. The article aims to offer answers to what conditions make it possible for those who inhabit the school to encounter. Experiential inquiry and phenomenology-hermeneutics are used as methodology. Reflective conversations were held with two teachers and the head teacher at a school located in a tough area. The conceptual elaboration is based on the empirical materials registered with the teachers. It shows some practical keys to create new relational dynamics that expand the welcoming power of the school. The conclusions show that the school disorganization that causes the difference becomes, through a process of composition and reinterpretation, an opportunity for the pedagogical encounter.